Analysis of Regional Regulation Number year 2015 Implementation on Urban Green Space Management in Mataram City - Dini Ardiantari, Lale; Ichsan, Andi Chairil; Webliana, Kornelia (Talenta Publisher, 2021)
Green open space is an area that has a function as well as a place to grow plants, both those that grow naturally and are planted. One way to improve environmental quality and revitalize urban ecosystems is by managing the Green Open Space. One of the alternatives supporting this effort is to make supportive and applicable policies, laws, and regulations. This research was conducted to examine the implementation of Regional Regulation Number 8 of 2015 regarding Green Open Space Management in Mataram City and to find out planning strategies in optimizing the implementation of applicable policies. The method used in this research is literature study method, interview, and observation. In this study, six criteria are used based on William N. Dunn's theory to analyze policies and SWOT analysis to determine the appropriate management strategy. The policy implementation analysis results show that the implementation of these regional regulations falls into the